Empirical lessons regarding contraception in a protracted refugee setting: A descriptive study from Maela camp on the Thai-Myanmar border 1996 – 2015 - Srikanok, Somjet; Parker, Daniel M.; Parker, Amber L.; Lee, Tracey; Min, Aung Myat; Ontuwong, Pranee; Oo Tan, Saw; Sirinonthachai, Supachai; McGready, Rose (PloS one, 2017)
Conflict settings and refugee camps can be chaotic places, with large and rapid population movements, exacerbated public health problems, and ad hoc health services. Reproductive health care that includes family planning is of heightened importance in such settings, however, funding and resources tend to be constrained and geared towards acute health services such as trauma management and infectious disease containment. Here we report on the complexities and challenges of providing family planning in a post-emergency refugee setting, using the example of the largest refugee camp on the Thai-Myanmar border, in existence now for over 30 years. Data from 2009 demonstrates an upward trend in uptake of all contraceptives, especially long acting reversible contraception (LARC) and permanent methods (e.g. sterilization) over time. Increased uptake occurred during periods of time when there were boosts in funding or when barriers to access were alleviated. For example a surgeon fluent in local languages is correlated with increased uptake of tubal ligation in females. These data indicate that funding directed toward contraceptives in this refugee setting led to increases in contraceptives use. However, contraceptive uptake estimates depend on the baseline population which is difficult to measure in this setting. As far as we are aware, this is the longest reported review of family planning services for a refugee camp setting to date. The lessons learned from this setting may be valuable given the current global refugee crisis.